Toll-Like Receptors and Prostate Cancer - Zhao, Shu; Zhang, Yifan; Zhang, Qingyuan; Wang, Fen; Zhang, Dekai (Frontiers in Immunology, 2014)
Prostate cancer is the second leading cause of cancer-related death in men after lung cancer. Immune responses clearly play a critical role in the tumorigenesis and in the efficacy of radiation therapy and chemotherapy in prostate cancer; however, the underlying molecular mechanisms are still poorly understood. Toll-like receptors (TLRs) are a well-known family of pattern recognition receptors that play a key role in host immune system. Recent studies demonstrate that there are links between TLRs and cancer; however, the function and biological importance of TLRs in prostate cancer seems complex. To elucidate the role of TLRs and innate immunity in prostate cancer might provide us with a better understanding of the molecular mechanisms of this disease. Moreover, utilizing the agonists or antagonists of TLRs might represent a promising new strategy against prostate cancer. In this review, we summarize recent advances on the studies of association between TLR signaling and prostate cancer, TLR polymorphisms and prostate cancer risk, and provide some insights about TLRs as potential targets for prostate cancer immunotherapy.